FASILITAS TRANSIT RAWA BUAYA - Cindy Herlim Santosa; Sidhi Wiguna Teh (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2020)
Jakarta is the second most populous city in the world with a population density of 10 million people in 2017. Density causes rapid development in the Jakarta area without any planning. The development that occurs makes the boundaries between office zoning located in the downtown area and residential zones located on the edge of the city. The zones formed have resulted in increased mobility that can be seen from vehicle ownership, transportation modes, and traffic congestion in Jakarta. Charles Montgomery in the book Happy City said that high congestion causes a decline in health that occurs due to stress for the community of public transportation modes. One way to reduce stress is to socialize according to Adhiatma and Christianto (2019). Third Place or social space becomes a solution for socializing for the public transportation community. The Third Place concept can be felt more by the public transportation community, where they can feel the difference between the housing zone and the office zone. The transit or transit place that is formed will be a social space that is used without differentiating social status. One of them is the transit facility located in Rawa Buaya. The Rawa Buaya transit facility is designed using qualitative data collection techniques and cross programming in design planning. The method used produces three main programs that emphasize service, entertainment and commercial functions, which shape social interaction, gathering space, and space for interaction between Rawa Buaya bus terminal communities. AbstrakJakarta merupakan kota kedua terpadat di dunia dengan kepadatan penduduk mencapai 10 juta jiwa pada tahun 2017. Kepadatan menimbulkan perkembangan yang cepat di wilayah Jakarta tanpa adanya perencanaan. Perkembangan yang terjadi membuat batasan antar zonasi perkantoran yang berada di daerah pusat kota dan zona hunian yang berada di pinggir kota. Zona yang terbentuk mengakibatkan peningkatan pergerakan mobilitas yang dapat dilihat dari kepemilikan kendaraan, pengguna moda transportasi, dan kemacetan yang terjadi di Jakarta. Charles Montgomery dalam buku Happy City mengatakan mengenai kemacetan yang tinggi menimbulkan penurunan kesehatan yang terjadi akibat stress bagi kaum komunitas moda transportasi umum. Salah satu cara mengurangi stress adalah dengan bersosialisasi menurut Adhiatma dan Christianto (2019). Third Place atau ruang sosial menjadi solusi untuk bersosialisasi bagi komunitas transportasi umum. Konsep Third Place dapat lebih dirasakan oleh komunitas transportasi umum, dimana mereka dapat merasakan perbedaan zona perumahan dengan zona perkantoran. Tempat transit atau tempat singgah yang terbentuk akan menjadi ruang sosial yang digunakan tanpa membedakan status sosial. Salah satunya fasilitas transit yang berada di Rawa Buaya. Fasilitas transit Rawa Buaya dirancang dengan menggunakan teknik pengumulan data kualitatif dan cross-programming dalam perencanaan perancangan. Metode yang digunakan menghasilkan tiga program utama yang menekankan pada fungsi pelayanan, hiburan, dan komersil, yang membentuk interaksi sosial, ruang berkumpul, dan ruang untuk berinteraksi antar komunitas terminal bus Rawa Buaya.